Synthesis, structural characterization, therotical and electrical properties of novel sulpho-coumarin based methacrylate polymer - Ozdemir, Mucahit; Biryan, Fatih; Koran, Kenan; Yalcin, Bahattin; Gorgulu, Ahmet Orhan (Springer, 2022)
In this study, a new coumarin-based methacrylate monomer was synthesized and its homopolymer P(SCou) was prepared by free radical polymerization method. The structural characterization of the compounds was performed by using FT-IR, H-1 and C-13-NMR spectroscopic techniques. The thermal behavior of the polymer was investigated by differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) methods. Thermal decomposition kinetics were investigated with TGA results at different heating rates by non-isothermal method. Thermal decomposition activation energy of homopolymer was calculated according to Flynn-Wall-Ozawa in the 5%-50% conversion range. The average activation energy of P(SCou) was found to be 220.21 kJ/mol. Theoretical calculations were done with Gaussian and the results were visualized with GaussView 5.0 and IQMol. Geometry optimizations of sulfocoumarin monomer and polymer were calculated with Becke-3-Lee-Yang-Parr's functional correlation (B3LYP). Optical band gaps for sulfonyl coumarin-(SCou), its monomer SCou-MA and P(SCou) compounds are 3.615, 3.723 and 3.792 eV, respectively. The dielectric properties of the polymer were investigated as a function of frequency and temperature in the frequency range of 1-200 kHz. Also, a heterojunction Shotky diode of the polymer was prepared on a p-type Si substrate using the thin-film technique. The I-V characteristic of the polymer/p-Si thin film heterojunction diode was determined between +/- 4 V and the various illumination intensities. The device has displayed good rectification behavior proving the creation of Schottky junction. The ideality factor was determined as 3.71, and the reverse supply current was determined as 8.78 x 10(-5) A.
Keywords: Coumarin; Homopolymer; Therotical properties; Electrical properties; Diode